Prevalence of Complications from Adult Tonsillectomy and Impact on Health Care Expenditures. (April 2014) - Seshamani, Meena; Vogtmann, Emily; Gatwood, Justin; Gibson, Teresa B.; Scanlon, Dennis
Objective: To provide information on the prevalence of common complications of adult tonsillectomy and associated health care utilization and expenditures. Study Design: Retrospective analysis of a large insurance database. Setting: Data from the MarketScan Commercial Claims and Encounters Database. Subjects and Methods: Treated prevalence rates for post-tonsillectomy complications were calculated for 36, 210 patients with employer-sponsored insurance who had an outpatient tonsillectomy between 2002 and 2007. The relationships with various patient characteristics were examined using multivariate logistic regression. Postoperative emergency department (ED) visits and hospitalizations and total per capita health care expenditures were analyzed. Results: This analysis suggests that of adult patients who undergo a tonsillectomy, 20% will have a complication, 10% will visit an ED, and approximately 1.5% will be admitted to a hospital within 14 days of the tonsillectomy. Six percent were treated for postoperative hemorrhage, 2% for dehydration, and 11% for ENT pain within 14 days of surgery. Patients with comorbidities, prior peritonsillar abscess, or an increased number of antibiotic prescriptions in the past year were significantly more likely to develop complications. Three out of 4 patients with postoperative hemorrhage went to the ED (4.63% of all patients), and 50% had a procedural intervention (3.09% overall). The average cost associated with a tonsillectomy was 3832 if no complication. If there was a complication within 14 days, hemorrhage was the most expensive (6388 vs 5753 for dehydration and 4708 for ENT pain). Conclusions: Complications of adult outpatient tonsillectomies are common and may be associated with significant morbidity, health care utilization, and expenditures.